Black phosphorus: Versatile two‐dimensional materials in cancer therapies. Issue 1 (27th August 2020) - Ding, Jie; Qu, Guangbo; Chu, Paul K.; Yu, Xue‐Feng
Abstract: Black phosphorus (BP) constitutes a new class of two‐dimensional materials with multiple biomedical functionalities and applications. Possessed with outstanding advantages of large surface area, intrinsic photoacoustic properties, excellent biocompatibility, and selective toxicity to tumor cells, BP is becoming an ideal candidate in multifunctional cancer theranostics including photothermal therapy, photodynamic therapy, drug delivery, and bioactive phosphotherapy. This minireview summarizes recent progress pertaining to theranostic applications of BP nanosheets and black phosphorus quantum dots and discusses the prospects in advanced theranostics. Abstract : As a fledgling class of 2D materials with excellent and unique properties, BPs have promising prospects in biomedical applications especially in cancer therapy. This mini‐review summarizes recent progress related to the application of BPs to different tumor therapies such as PTT, PDT, RT, BPT and diagnosis‐combined therapy.